Pengaruh Konservatisme Akuntansi, Pertumbuhan Perusahaan dan Risiko Bisnis terhadap Income Smoothing - Nona Jane Onoyi; Ely Kurniawati; One Yantri; Diana Titik Windayati (Reviu Akuntansi, Manajemen, dan Bisnis, 2023)
Purpose: This study aims to determine the effect of accounting conservatism, company growth and business risk toward income smoothing. This study uses accounting conservatism, company growth and business risk as independent variables. While income smoothing is the dependent variable. The research population is a coal mining company listed on the IDX as 22 companies. The research sample consisted of 9 companies obtained by using the purposive sampling method. The research sample consisted of 9 companies obtained by using the purposive sampling method Methodology/approach: The research method uses multiple linear regression. Results/findings: The results showed that partially the accounting conservatism variable and the firm growth variable did not have any significant effect on income smoothing, while the business risk variable had a significant effect on income smoothing. Simultaneously accounting conservatism variables, company growth and business risk have a significant effect on income smoothing. Advice for companies is to maintain business risk in order to keep investor confidence in the company.